Factores maternos e institucionales y desarrollo psicomotor del preescolar, Alto Trujillo - Gasco Rosales, Georgette Alejandra (2020)
This quantitative, explanatory, correlational and cross-sectional research was carried out during the month of October to December of 2019, with the purpose of determining the relationship between Maternal and Institutional Factors and Psychomotor Development in Preschoolers. The sample consisted of 146 preschoolers of the C.S. "Melvin Jones." For the data collection, the 2 - 5-year psychomotor development test (TEPSI) was used, a “Maternal knowledge level on early preschool stimulation and a questionnaire on institutional factors of the growth and development program”. The results are presented in statistical tables. It is concluded with respect to maternal factors that 85.6% are young adult mothers, 72.6% are housewives, 45.9% have full secondary education and 64.2% have a medium level of knowledge about early stimulation; Regarding institutional factors, 57.5% consider the location as close, 65.8% consider the hours of care adequate, 76% consider that there isn’t difficulty in accessibility to appointments, 59.6% consider nursing staff to be insufficient, 53.4% consider the quality of care as good, 75.3% consider the attention time sufficient, 76.7% consider the infrastructure adequate, 80.8% consider the information easy to understand and 82.9% consider the appropriate cost finally the psychomotor development of preschoolers 55.5% is normal, 22.6% is at risk of delay and 21.9% late.